ELECTROMYOGRAPHIC COMPARISON OF SQUASH FOREHAND SHOT AFTER MIDCOURT AND FRONTCOURT TRADITIONAL MOVEMENT PATTERNS - Tarek G. Alaaeldien,; Abdel-Rahman I. Akl, (Sport Scientific And Practical Aspects, 2025)
Electromyography of sixteen muscles of the lower limb, trunk, and upper limb muscles were compared between forehand shot after traditional midcourt movement pattern and traditional frontcourt movement pattern of a three female squash players (age: 14.5±0.5 years old; height 1.48±0.15 m; mass: 44.67±1.53 Kg), ranked in the Squash National Egyptian team. Surface electromyographic (sEMG) electrodes were placed according to SENIAM guidelines on the skin, superficial to right-sided postural proximal of the trapezius, posterior deltoid, anterior deltoid, triceps brachii, biceps brachii, pectoralis major, serratus anterior, rectus abdominis, external abdominal, glutaeus medius, gluteus maximus, biceps femoris, rectus Femoris, tibialis anterior, gastrocnemius, and soleus muscle. EMG data were 16 bit A/D converted at 1000 Hz and stored on computer. EMG signals were amplified (gain of 400), band pass filtered (10 to 500Hz), full wave rectified using root mean square average, and normalized to the isometric muximum voluntary contraction (MVC). Mean and standard deviation of the muscle activity and work-loading were calculated from the start of the two tasks to the end of forehand shot recovery phase. The results showed that the difference between the Forehand shot after traditional midcourt movement pattern and Forehand shot after traditional frontcourt movement pattern in pectoralis major muscle and rectus abdominis muscle, and no differences existed in the other selected muscles. The study determined the muscle activity (% MVC) for the sixteen selected muscles during the two patterns of forehand shots, and the percentage of work-loading (% Total activity area) for each muscle.